Language, Quantum, Music - Dalla Chiara, Maria Luisa; Giuntini, Roberto; Laudisa, Federico; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1999)
A vivid and comprehensive picture of the current state of research in all directions of logic and philosophy of science. The book presents a wide combination of papers containing relevant technical results in the foundations of science and papers devoted to conceptual analyses, deeply rooted in advanced present-day research. Audience: The volume is attractive both for specialists in foundational questions and scholars interested in general epistemology.
I: Epistemology and Philosophy of Language -- Realism, Idealism, and General Terms -- From Formal Machine to Social Colony: Toward a Complex Dynamical Philosophy of Science -- Observation and Reliable Detection -- Conceptual Idealism and Stove s Gem -- Holism in Artifical Intelligence -- II: Philosophy of Probability -- Model Selection for Causal Theories -- Nonstandard Analysis and a Classification of Probability Spaces -- Some Remarks on Objective Chance (F.P. Ramsey, K.R. Popper and N.R. Campbell) -- Misapprehensions about Significance Tests and Bayesianism -- III: Philosophy and Foundations of Physics -- The Quantum Probabilistic Approach to the Foundations of Quantum Theory: Urns and Chamaleons -- The Creation-Discovery-View: Towards a Possible Explanation of Quantum Reality -- Virtual Reality: Consequences of No-Go Theorems for the Modal Interpretation of Quantum Mechanics -- Is Chaos Indeterministic? -- Wormholes and Timelike Curves: Is There Room for the Grandfather Paradox? -- John von Neumann met Kurt Gödel: Undecidable Statements in Quantum Mechanics -- Set-Theoretical Models for Quantum Systems -- Non-Ideal Measurements and Physical Possibility in Quantum Mechanics -- Time, Relativity, and the Spatiality of Mental Events -- Bell-Type Inequalities and Orthomodular Lattices -- An Informal Presentation of Semantic Realism and Its Solution of Quantum Paradoxes -- Individualistic Versus Statistical Interpretation of Quantum Mechanics -- The Locality Scandal of Quantum Mechanics -- Uncertainty and Dependence in Classical and Quantum Logic the Role of Triangular Norms -- Quantum Logics and Quantum Measurements -- Attempt at the Logical Explanation of the Wave-particle duality -- IV: History of Science -- The Bohr-Einstein Photon Box Debate -- Kantianism and Physics from the 19th to the 20th Century -- V: Science and Music -- Epimoric Ratios and Greek Musical Theory -- Music and Science.
Keywords: Philosophy and science; Quantum physics; Physics; Epistemology; Music; Philosophy of Science; Quantum Physics; History and Philosophical Foundations of Physics; Epistemology; Music